Vitrectomy for a traumatic macular hole caused by cosmetic laser in a beauty salon: A case report - Songyue Yang; Chunyan Lei; Meixia Zhang (Heliyon, 2024)
Background: The Nd:YAG laser is widely used in various aspects of work and life. Currently, it has become a popular cosmetic technique in beauty salons. The laser can be dangerous when it flashes into people's eyes. Case presentation: A 34-year-old female sustained a 1064-nm Q-switched Nd:YAG laser injury to her left eye. One month after the injury, she presented to our clinic with best-corrected visual acuity (BCVA) of 20/250 and a full-thickness macular hole on the optical coherence tomography (OCT). The patient received pars plana vitrectomy, internal limiting membrane peeling and sterile air injection 3 months after the injury. OCT showed closure of the hole 9 days postoperatively. After a 3-month follow-up, her BCVA improved to 20/100. Conclusions: This case report comprehensively introduces the whole progression of a cosmetic laser-induced macular hole from formation to recovery. Due to the potential threats of the laser and its irreversible damage to the retina and choroid, sufficient education should be given before performing any laser devices, especially those without professional knowledge.